ANALISIS KONSEP WAKAF SEBAGAI SUMBER PEMBIAYAAN UNTUK BARANG PUBLIK DAN BARANG PUBLIK CAMPURAN DI INDONESIA - Rahman, Moh Abd (universitas Islam Zainul Hasan Genggong, 2025)
This study aims to formulate a model of waqf invested in public goods and mixed public goods in Indonesia. This model is built based on an understanding of the concept of waqf, lessons learned from past and present waqf institutions, and addressing waqf issues in Indonesia. This study uses qualitative descriptive research with a literature review method. This study uses secondary data from the Indonesian Waqf Board (BWI), books, journals, bulletins, government reports, and websites. The findings of this research indicate that the benefits of implementing invested endowment funds can assist the state treasury in the form of public goods and mixed public goods. The entire process can be managed by endowment institutions as endowment trustees collaborating with the Indonesian Endowment Agency (BWI) in overseeing the use of government endowment assets, ensuring expenditures align with sharia regulations. This research demonstrates how practical wakaf can assist the Indonesian government in financing public goods and mixed public goods. This indirectly indicates the existence of alternative funding sources for such goods. The application of the wakaf concept can learn and adapt from the model developed in this paper.